Effect of Investment Decisions, Funding Decisions and Dividend Policy on Firm Value with Firm Risk as Mediation on Manufacturing Companies Listed on the Indonesia Stock Exchange (IDX) - MUHAMMAD KURNIA SHANDY; AIMATUL YUMNA (Financial Management Studies, 2022)
The study aims to analyze the effect of (1) Investment Decisions on company risk, (2) Funding decisions on company risk and (3) Dividend policy on company risk. (4) Investment decisions on company value, (5) Funding decisions on firm value (6) Dividend policy on firm value (7) Corporate risk on firm value (8) Investment decisions, funding decisions and dividend policy on firm value by mediating firm risk. with Manufacturing performance proxies listed on the Indonesia Stock Exchange in 2017-2021. The study used one control variable: firm value and one mediating variable: firm risk. The population in this study is all manufacturing companies listed on the Indonesia Stock Exchange. While the samples in the study were determined by the purposive sampling method, the Manufacture company's samples for three consecutive years from 2017-2021, resulting in a samples count of 33 companies with 193 observations for each variable. The analysis method used path analysis using the IBM SPSS Statistics 26 program. The results of this study concluded that (1) investment decisions with PER have no effect on company risk, (2) DER funding decisions have a significant effect on company risk, (3) dividend policy has a significant effect on company risk (4) investment decisions with PER have an effect on firm value (5) Funding decisions with DER have no effect on firm value (6) Dividend policy with DPR has no effect on firm value (7) Company risk with DCL has no effect on firm value (8) Investment decisions with PER through corporate risk mediation has no effect on firm value (9) Funding decisions with DER through firm risk affect firm value (10) Dividend policy with DPR through firm risk does not affect firm value